2007
DOI: 10.1007/s11632-007-0025-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the forest ecosystem health in Beijing area

Abstract: The evaluation of ecosystem health has become one of the main research topics of ecosystem science, thus more and more assessment methods and frameworks have been put forward in recent years. However, the attention people pay to ecosystem health is actually more about what the social functions the ecosystem affords, which depend on the integrity and maintenance of the ecosystem structure and function, and the intensity of disturbance from outside. Accordingly, this research commenced from three main aspects, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…There are six musk deer (Moschidae) species in the world (Jiang et al 2015), and all are famous for the musk secreted by the male gland, a precious traditional Chinese medicine and a superior component in perfume production (National Pharmacopoeia Committee 2015). However, due to over-exploitation and habitat fragmentation, the wild musk deer populations plummeted from 2.5 million in the 1950s to 66,300 in the year 2000 (Sheng and Liu 2007; Ma and Zhang 2009), and each species has been listed on the Category I of the State Key Protected Wildlife List of China. Artificial breeding is an effective way to protect musk deer, in that it is beneficial to population growth and that it can mitigate the poaching pressure on wild populations.…”
mentioning
confidence: 99%
“…There are six musk deer (Moschidae) species in the world (Jiang et al 2015), and all are famous for the musk secreted by the male gland, a precious traditional Chinese medicine and a superior component in perfume production (National Pharmacopoeia Committee 2015). However, due to over-exploitation and habitat fragmentation, the wild musk deer populations plummeted from 2.5 million in the 1950s to 66,300 in the year 2000 (Sheng and Liu 2007; Ma and Zhang 2009), and each species has been listed on the Category I of the State Key Protected Wildlife List of China. Artificial breeding is an effective way to protect musk deer, in that it is beneficial to population growth and that it can mitigate the poaching pressure on wild populations.…”
mentioning
confidence: 99%
“…The China Forest Association Committee (1982) concluded that runoff depth increased 0.4-1.1 mm when forest cover rate improved each 1% based on investigation of three controlled groups of hilly watersheds in North China under the same conditions of climate, geology and topography. Zhang (1984) and Ma (1993) noted similar results after investigating more than forties watersheds in North China. From the above, it can be observed that the contradictive conclusions from previous studies were due to the limitations of research methodologies, the complexities of research objects and the differences of regions and scales of watersheds.…”
Section: Introductionmentioning
confidence: 59%
“…The second view declared that forestation resulted in increased water yield. Ma (1993) stated that water yield increased 114 mm higher in forest covered watershed than less or non-forest covered watershed in Volga River Basin and watersheds around Caspian Sea and Baltic Sea in Russia, and annual water yield increased 1.5-2.8 mm when forest cover rate improved 1%. Jing (1989) found that water yields in forest covered watersheds were 21.8-32.8% higher than non-forest covered watersheds in Changjiang River Basin.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason was the capacity of water retention by terrestrial ecosystem during transitional period from low-flow to high-flow. Many results have indicated that the capacity of water retention is closely related to vegetation, soil and slope (Lee, 1980;Ma, 1993;Guo and Gan, 2002 EGU subalpine coniferous forests had more power in increasing the soil organic matter, improving the soil construction, receding soil bulk density and enhancing the soil porosity than the alpine shrubs and meadows (Chang et al, 2003), the soil of subalpine coniferous forests had the highest water holding capability. Meanwhile, the velocity of melting water, mainly including snow and soil water meltings , in the southfacing slopes was higher than those in the north-facing slopes during transitional period from low-flow to high-flow, and the subalpine coniferous forests mainly distributed in the north-facing slopes, the alpine shrubs dominated the south-facing slopes and the alpine meadows common on the top of the mountains (Sichuan Vegetation Editing Committee, 1980;Jiang et al, 2004), So the water yield was positive correlation with vegetation cover patterns in the south-facing slopes and negative correlation with the forest cover in the north-facing slopes.…”
Section: Egu 5 Discussionmentioning
confidence: 99%